Podcast Youtube sebagai Media Dakwah Digital: Transformasi Strategi Penyiaran - Ahmad Mirzaq; Mahfudz Mahfudz (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
The development of digital media has encouraged a shift in da’wah strategies from conventional broadcasting patterns toward online platform-based communication that is more interactive, flexible, and participatory. This study aims to describe the use of YouTube podcasts as a digital da’wah medium in supporting the transformation of broadcasting strategies among Islamic Communication and Broadcasting students at Universitas Nurul Jadid. This study uses a descriptive qualitative method with a digital content analysis approach. Data were obtained through observation of YouTube podcast content, digital documentation, audience comment analysis, and interviews with content creators or managers. The analysis was conducted on relevant da’wah and Islamic podcast channels as comparative data, with the main focus on the da’wah broadcasting practices of KPI students at Universitas Nurul Jadid. YouTube statistical data, such as the number of views, likes, comments, and audience engagement, were used as descriptive supporting data rather than as a basis for statistical testing. The findings show that the effectiveness of YouTube podcasts as a digital da’wah medium is influenced by audio-visual production quality, communication models, topic relevance, upload consistency, and audience responses. Inspirational and participatory communication models tend to be more effective because they are able to build emotional closeness, present messages communicatively, and align da’wah materials with the lives of young audiences. In addition, YouTube podcasts encourage the transformation of students’ roles from merely delivering messages to becoming digital da’wah content producers who are involved in planning, production, publication, and content evaluation. This study concludes that YouTube podcasts have the potential to serve as a digital da’wah medium as well as a broadcasting practice laboratory for KPI students. The development of YouTube podcasts needs to be directed toward improving production quality, selecting contextual topics, maintaining publication consistency, and utilizing YouTube analytics as a basis for evaluating digital da’wah.